Non-destructive 3D internal structure analysis of sedimentary samples using high-resolution X-ray computed tomography - Chae, Yong-Un; Kang, Seong-Seung; Ha, Sujin; Joo, Young Ji; Lim, Hyoun Soo (Frontiers in Earth Science, 2025)
X-ray computed tomography (X-ray CT), initially developed for medical applications, has undergone continuous advancements and is now widely used in industrial and geological research as a high-resolution imaging technique. In this study, we utilized X-ray CT to visualize, extract, and quantitatively measure (volume and anisotropy) the internal structures of rod-shaped stromatolites, invertebrate burrow-bearing rocks, and deformed cobbles derived from the Cretaceous Gyeongsang Basin, Korea. Our results demonstrate that, when there is a sufficient contrast in density and/or particle size between internal structures and their surroundings, X-ray CT reliably reveals and enables quantitative analysis of these structures with high precision. However, in cases where attenuation contrast is insufficient, imaging limitations may arise. Despite these constraints, X-ray CT provides significant advantages over traditional 2D observations by enabling a non-destructive, high-resolution analysis of internal structures. This study highlights the necessity of applying X-ray CT analysis more extensively to various geological samples for a more accurate and intuitive understanding of internal structures.